Legal Socialization Strategy in Expanding Understanding of Postnuptial Agreements for Indonesian Citizens in Taiwan - Andhari Putri, Arsetty; Prahasti Suyaman, Prahasti Suyaman (KRTHA BHAYANGKARA, 2025)
This study discusses legal socialization strategies in expanding the understanding of postnuptial agreements for Indonesian Citizens (WNI) in Taiwan. A postnuptial agreement is an important legal instrument to regulate the rights and obligations of husband and wife, especially in terms of property management, both during the marriage period and in the event of divorce. However, understanding of the existence and benefits of this agreement is still low among the Indonesian diaspora. This study uses a sociological juridical method with a qualitative approach, which not only examines the normative aspects of marriage law, but also explores the social realities that affect the effectiveness of the dissemination of legal information abroad. The results of the study show that the lack of socialization, limited access to information, and differences in legal and cultural contexts are the main obstacles in the dissemination of legal understanding. Therefore, an integrated legal socialization strategy such as online seminars, integrated counseling, social media, and the provision of Indonesian legal materials in accordance with the local context is urgently needed. With this strategy, it is hoped that Indonesian citizens in Taiwan can better understand their rights under marriage law and be encouraged to make post-marriage agreements consciously and legally. This research emphasizes the importance of collaboration between governments, foreign representatives, legal practitioners, and diaspora communities in creating inclusive and sustainable legal literacy.